Validity of the Néel-Arrhenius model for highly anisotropic CoxFe3−xO4 nanoparticles - Torres, T.E. (2015)
We report a systematic study on the structural and magnetic properties of CoxFe3−xO4 magnetic nanoparticles with sizes between 5 and 25 nm, prepared by thermal decomposition of Fe(acac)3 and Co(acac)2. The large magneto-crystalline anisotropy of the synthesized particles resulted in high blocking temperatures (42 K < TB < 345 K for 5 < d < 13 nm) and large coercive fields (HC ≈ 1600 kA/m for T = 5 K). The smallest particles (⟨d⟩=5 nm) revealed the existence of a magnetically hard, spin-disordered surface. The thermal dependence of static and dynamic magnetic properties of the whole series of samples could be explained within the Neel?Arrhenius relaxation framework by including the thermal dependence of the magnetocrystalline anisotropy constant K1(T), without the need of ad-hoc corrections. This approach, using the empirical Brükhatov-Kirensky relation, provided K1(0) values very similar to the bulk material from either static or dynamic magnetic measurements, as well as realistic values for the response times (τ0 ≈ 10−10s). Deviations from the bulk anisotropy values found for the smallest particles could be qualitatively explained based on Zener´s relation between K1(T) and M(T).